Student engagement in massive open online courses. (2016) - Sinclair, Jane; Kalvala, Sara
Completion rates in massive open online courses (MOOCs) are disturbingly low. Existing analysis has focused on patterns of resource access and prediction of drop-out using learning analytics. In contrast, the effectiveness of teaching programs in traditional higher education (HE) settings internationally is increasingly assessed by surveys measuring student engagement. The conceptualisation of engagement used is much richer and more informative than the way the term is currently interpreted in the context of MOOCs. This paper considers MOOC participation, learning and drop-out in the context of this richer conceptualisation of student engagement. MOOC pedagogy and practice are examined and we evaluate how far HE engagement measures can be successfully used in the MOOC context. We identify the need for a MOOC engagement model and suggest recommendations for basic, initial steps which MOOC developers can make towards improving engagement.